Interaction of gut microbiota with the tumor microenvironment: A new strategy for antitumor treatment and traditional Chinese medicine in colorectal cancer - Li, Tingting; Han, Liang; Ma, Simin; Lin, Weiji; Ba, Xin; Yan, Jiahui; Huang, Ying; Tu, Shenghao; Qin, Kai (Frontiers in Molecular Biosciences, 2023)
Colorectal cancer (CRC) is one of most common malignancies in the world and the second leading cause of cancer-related death. In recent years, the relationship between gut microbiota and CRC has attracted more and more attention from researchers. Studies have found that changes in the composition of the gut microbiota, such as the increase in the number of Fusobacterium nucleatum and Helicobacter hepaticus, impair the immune surveillance by affecting the intestinal mucosal immunity, thereby increasing the risk of tumor initiation and progression. The tumor microenvironment is the soil on which tumors live, and the close contact between the gut microbiota and the tumor microenvironment may directly affect the progression of tumors and the efficacy of antitumor drugs, thereby affecting the prognosis of CRC patients. In recent years, many studies have shown that traditional Chinese medicine(TCM) can safely and effectively improve the efficacy of antitumor drugs, and one of the mechanisms may be to affect the remodeling of the tumor microenvironment by the gut microbiota. This article describes the role of gut microbiota on the tumor microenvironment and the possible mechanisms affecting the initiation and progression of CRC, and summarizes the potential role of TCM.